2008
DOI: 10.1021/ja806244b
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Coupling Reactions of Aryl Pivalates with Boronic Acids

Abstract: The first cross-coupling of acylated phenol derivatives has been achieved. In the presence of an air-stable Ni(II) complex, readily accessible aryl pivalates participate in the Suzuki-Miyaura coupling with arylboronic acids. The process is tolerant of considerable variation in each of the cross-coupling components. In addition, a one-pot acylation/cross-coupling sequence has been developed. The potential to utilize an aryl pivalate as a directing group has also been demonstrated, along with the ability to sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
163
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 362 publications
(170 citation statements)
references
References 17 publications
1
163
1
5
Order By: Relevance
“…[1] During the past decade, enormous effort has been undertaken, especially in ligand design, [2] to enhance the capability of utilizing relatively inert electrophiles, such as aryl chlorides, [3] tosylates, [4] mesylates, [5] and pivalates, [6] as coupling partners. Yet, investigations on the development and application of new nucleophilic partners in cross-coupling reactions remain limited.…”
mentioning
confidence: 99%
“…[1] During the past decade, enormous effort has been undertaken, especially in ligand design, [2] to enhance the capability of utilizing relatively inert electrophiles, such as aryl chlorides, [3] tosylates, [4] mesylates, [5] and pivalates, [6] as coupling partners. Yet, investigations on the development and application of new nucleophilic partners in cross-coupling reactions remain limited.…”
mentioning
confidence: 99%
“…The variety of functional groups on these products provide a great opportunity for further functionalization with various methods. [15] However, the ortho-methoxy-substituent product terminated the transformation, which supposedly resulted from the chelating ability of the substrates.…”
mentioning
confidence: 99%
“…[5] Very recently, our group and Garg independently reported that aryl carboxylates could couple with arylboronic acid derivatives via Ni catalysis. [6] Following studies indicated that coupling of aryl pivalates with organozinc reagents and alkyl Grignard reagents could take place under even milder conditions. [7] This transformation was further expanded to alkenyl pivalates to afford styrene derivatives.…”
mentioning
confidence: 99%